Work–family demands and support: Examining direct and moderating influences on work–family conflict. (2nd April 2016) - Annor, Francis
ABSTRACT: This study examined the direct and moderating influences of work and family demands and support on work–family conflict among employees ( N = 154) in a public university in Ghana. Results showed that work pressure positively predicted work-to-family conflict, whereas family pressure positively predicted work-to-family conflict and family-to-work conflict. Contrary to expectation, work support was not significantly related to work–family conflict, whereas family support positively predicted both directions of work–family conflict. The results also suggested limited moderating effects of work and family support on the relationship of work and family demands with work–family conflict, with social support strengthening the impact of work–family demands on work–family conflict. Implications for work–family research and policy in the Ghanaian and sub-Saharan African contexts are discussed.